Lower prevalence of anti‐HTLV‐1 as expected by previous models among first‐time blood donors in Japan. Issue 3 (2nd March 2023) - Satake, Masahiro; Sagara, Yasuko; Hamaguchi, Isao
Abstract: An estimated 1.08 million carriers of human T‐lymphotropic virus 1 (HTLV‐1) were living in Japan in 2006–2007. Since that study, new data on horizontal infection, nationwide antenatal screening for anti‐HTLV‐1 in pregnant women, and social educational campaigns on HTLV‐1 infection have emerged in Japan. To estimate the current number of HTLV‐1 carriers in Japan, confirmed HTLV‐1 infections among first‐time blood donors in 2020–2021 from across Japan were investigated. Age‐, sex‐ and geographic area‐specific information associated with HTLV‐1 antibody detection was evaluated. Data obtained were compared with predictions based on 2006–2007 data, considering a birth cohort effect that assumed lifelong maintenance of seropositivity. HTLV‐1 seroprevalence in women was almost equivalent to that in men. The prevalence in men was similar to that predicted from 2006 to 2007 data. In contrast, the prevalence in women was lower in all age strata than that predicted by each birth cohort. The estimate for the entirety of Japan was 534 000 carriers from measured prevalence, whereas that from the birth cohort effect‐adjusted prevalence was 658 000. The number of HTLV‐1 carriers in Japan was estimated to have decreased by approximately 40% during the past 14 years.